2004
DOI: 10.1142/s0217751x04018713
|View full text |Cite
|
Sign up to set email alerts
|

Phase Shifts and Resonances in the Dirac Equation

Abstract: We review the analytic results for the phase shifts δ l (k) in non-relativistic scattering from a spherical well. The conditions for the existence of resonances are established in terms of time-delays. Resonances are shown to exist for p-waves (and higher angular momenta) but not for s-waves. These resonances occur when the potential is not quite strong enough to support a bound p-wave of zero energy. We then examine relativistic scattering by spherical wells and barriers in the Dirac equation. In contrast to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…General results are given in Ref. [23], where Eq. (62) for the s-wave particular case however contains several misprints.…”
Section: Square-well Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…General results are given in Ref. [23], where Eq. (62) for the s-wave particular case however contains several misprints.…”
Section: Square-well Potentialmentioning
confidence: 99%
“…These restrictions can both be overcome with some extra effort. In this case, the components of the external solution at energy E are approximated by the asymptotic form of the solutions [23],…”
Section: Internal and External Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 shows the behavior of the phase shift δ as a function of the real part of the resonant energy, it can be observed that the phase shift increases surpassing the value π/2 and after reaching a maximum, it monotonically decreases, showing in this way a behavior that has been observed in square well case. [15] …”
Section: Transmission Amplitude and Phase Shiftsmentioning
confidence: 99%
“…Analytic solutions have been obtained for the the square well [2,3], Woods-Saxon potential [4], cusp potential [5], and Hulthén potential [6] as well as asymmetric barriers [7,8], multiple barriers [9], and a class of short-range potentials [10]. The successful isolation of graphene [11] has led to renewed interest in the transmission-reflection problem for the one-dimensional Dirac equation.…”
Section: Introductionmentioning
confidence: 99%